The impact of the jurisprudence rules on the issues of gathering Halal and Haram and its contemporary - Saman, Ali ihsan; Nooruddin, Farooq Abbas; Omar, Arkan H. (Journal of Islamic Sciences, 2020)
The study came to highlight and show "the effect of doctrinal rules on the issues of halal and forbidden meeting and its contemporary applications." For this reason, the study was divided into two subjects, the definition of halal and haram was defined, and the meaning of each of them was explained to the jurists. And in the convention and when jurists The rules of halal and haram meeting are described, their sections and areas of application in terms of their formulas, their authenticity, their divisions and the fields of contemporary applications of the rules of halal and prohibited meeting. The study recommended that interest in building contemporary issues on its counterparts is one of the heritage issues mentioned in the books of jurists, as well as increasing consideration in building heritage issues on its jurisprudential rules mentioned by jurists.